2010
DOI: 10.1007/s00467-010-1532-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency results in dysregulation of lipid efflux pathway in rat kidney

Abstract: The mechanisms of action of vitamin A deficiency (VAD) on lipid metabolism in the rat kidney were investigated in adult female rats and their offspring. The rats were randomized into three groups: (1) control, in which the mother and offspring received a normal diet (4000 retinol IU/kg diet) for 8 weeks; (2) VAD group, in which the mothers and offspring received a VAD diet (400 retinol IU/kg diet) for 8 weeks; (3) vitamin A-refed group, in which a group of pups on a VAD diet for 8 weeks received a complete die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Moreover, TGF-β1, via an integration of the Smad3 and STAT3 signalling pathways stimulates the connective tissue growth factor (CTGF), a central mediator of ECM production. In agreement, increased levels of TGF-β1 have been found in VAD tissues such as kidney, lung and aorta [ 32 , 123 , 186 , 188 , 189 , 190 , 191 , 192 , 193 ].…”
Section: Vitamin a Deficiency And The Lungsupporting
confidence: 63%
“…Moreover, TGF-β1, via an integration of the Smad3 and STAT3 signalling pathways stimulates the connective tissue growth factor (CTGF), a central mediator of ECM production. In agreement, increased levels of TGF-β1 have been found in VAD tissues such as kidney, lung and aorta [ 32 , 123 , 186 , 188 , 189 , 190 , 191 , 192 , 193 ].…”
Section: Vitamin a Deficiency And The Lungsupporting
confidence: 63%
“…It has also been suggested that prenatal exposure to VAD may be a factor that contributes disproportionately to rising kidney disease incidence in disadvantaged populations [ 97 , 98 ]. It has also been found that VAD induces significant alterations in renal lipid metabolism and immune status, may contribute to the development of idiopathic kidney stones and may worsen renal diseases such as pyelonephritis [ 99 , 100 , 101 ]. The beneficial effect that retinoids have on several renal disorders, and their antifibrotic and cytoprotective effect on different types of renal cells [ 91 , 102 ], have also been demonstrated, which supports the importance of vitamin A for proper kidney development and for maintaining its integrity and function.…”
Section: Vitamin a Deficiency And Alterations In Extracellular Matmentioning
confidence: 99%
“…All these processes potentially lead to ECM overproduction. Increased TGF-β1 levels have been found in VAD tissues, such as kidney [ 101 ], lung [ 138 ], and aorta [ 173 ]. Therefore, signaling by this profibrotic factor can also mediate in ECM modifications.…”
Section: Mechanism Of Extracellular Matrix Modifications In Vitamimentioning
confidence: 99%
“…In developing countries, vitamin A deficiency is still a serious and widespread public health problem among pregnant women and children. Vitamin A also has an effect on energy metabolism, adipocyte differentiation, and lipid metabolism in different organs [109], including the kidney [110]. Animal studies have shown that mild vitamin A deficiency leads to inborn nephron deficit in the rat [108].…”
Section: Effects Of Maternal Nutrition On Renal Developmentmentioning
confidence: 99%